THE EFFECT OF SOCIAL REHABILITATION ON LEGAL AWARENESS OF DRUG PRISONERS IN CLASS I CORRECTIONAL INSTITUTION SURABAYA - Fariandra, Mas Varis Simba Putra; Dr. Karim (jfpublisher, 2023)
Law No. 35/2009 Article 54 on narcotics clearly states that narcotics addicts and victims of narcotics abuse must receive medical rehabilitation and social rehabilitation. Drug addiction does not instantly disappear, therefore rehabilitation is needed before they are admitted into the development phase. Not only as a place for the development of prisoners, the correctional institution is also a suitable place to rehabilitate drug prisoners, as is the case in Class I Correctional Institution Surabaya. Therefore, this research is conducted to find out the implementation of social rehabilitation for drug prisoners in Class I Correctional Institution Surabaya; and to find out the effect of social rehabilitation on legal awareness of drug prisoners there. The type of this research is descriptive qualitative combined with juridical-empirical approach. The researcher used primary and secondary data to collect the data. Primary data was obtained from the development and security section at Class I Correctional Institution Surabaya, while secondary data was obtained from literature review derived from regulations and laws related to the research topic. The implementation of social rehabilitation at Class I Correctional Institution Surabaya is in accordance with the Correctional Rehabilitation Service Provider Standards issued by the Directorate General of Corrections in 2020; and Regulation of the Minister of Law and Human Rights of Indonesia No. 12/2017 on the Implementation of Narcotics Rehabilitation for Prisoners. The programs provided during the social rehabilitation are very effective on the legal awareness of drug prisoners. Social rehabilitation include psychological and social aspects. These programs directly affect their understanding of the surrounding environment. From the research results, it is concluded that increased law enforcement against drug trafficking helps prevent drug consumption. The quality and quantity of correctional officers need to be supported to assist the implementation of assistance in prisons to be even more effective.